2015
DOI: 10.1158/0008-5472.can-15-1877
|View full text |Cite
|
Sign up to set email alerts
|

UV-Associated Mutations Underlie the Etiology of MCV-Negative Merkel Cell Carcinomas

Abstract: Merkel cell carcinoma (MCC) is an uncommon, but highly malignant, cutaneous tumor. Merkel cell polyoma virus (MCV) has been implicated in a majority of MCC tumors; however, viralnegative tumors have been reported to be more prevalent in some geographic regions subject to high sun exposure. While the impact of MCV and viral T-antigens on MCC development has been extensively investigated, little is known about the etiology of viralnegative tumors. We performed targeted capture and massively parallel DNA sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
278
1
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(321 citation statements)
references
References 21 publications
16
278
1
18
Order By: Relevance
“…Specifically, several recent studies have shown that MCPyV-negative MCCs have a very high mutation burden (median 1,121 somatic single nucleotide variants per exome). These are dominated by C > T transitions, characteristic of UV-induced DNA damage [88][89][90]. This UV-induced signature was not observed in MCPyV-positive tumors and the mutation burden was 19-fold lower (median 12.5 somatic single nucleotide variants per exome) indicating that these tumor types arise through distinct mechanisms [88][89][90].…”
Section: Virus-negative Mccs and Uv-induced Neoantigensmentioning
confidence: 93%
See 2 more Smart Citations
“…Specifically, several recent studies have shown that MCPyV-negative MCCs have a very high mutation burden (median 1,121 somatic single nucleotide variants per exome). These are dominated by C > T transitions, characteristic of UV-induced DNA damage [88][89][90]. This UV-induced signature was not observed in MCPyV-positive tumors and the mutation burden was 19-fold lower (median 12.5 somatic single nucleotide variants per exome) indicating that these tumor types arise through distinct mechanisms [88][89][90].…”
Section: Virus-negative Mccs and Uv-induced Neoantigensmentioning
confidence: 93%
“…Conversely, several others have reported no significant survival difference between the two groups [85][86][87]. Importantly, genetic analysis indicates that these two subsets are etiologically distinct [88][89][90]. Specifically, several recent studies have shown that MCPyV-negative MCCs have a very high mutation burden (median 1,121 somatic single nucleotide variants per exome).…”
Section: Virus-negative Mccs and Uv-induced Neoantigensmentioning
confidence: 96%
See 1 more Smart Citation
“…MCPyV is a DNA virus that likely mediates tumorigenesis via large T antigen (LTAg) binding to the tumor suppressor RB1 and small T antigen (sTAg) upregulation of oncoprotein stability and mTOR activation (1,2). Unlike MCPyV-positive tumors, MCPyV-negative MCC tumors display high mutation burdens, TP53 and RB1 mutations, and UV-signature mutational profiles, suggesting a molecular dichotomy between MCPyV-positive and MCPyV-negative tumors that may have translational relevance (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Etwa 80 % der MZK sind assoziiert mit dem Merkelzell-Polyomavirus (MCPyV), das 2008 identifiziert wurde [15]. Die übri-gen 20 % der MZK sind MCPyV-negativ und zeichnen sich durch charakteristische UV-assoziierte Schäden auf genomischer Ebene aus [16,17] "Prä-/pro-B-Zell"-Hypothese: B-Vorläuferzellen als zellulärer Ursprung der Merkelzellkarzinome Sowohl der morphologisch blastäre Phä-notyp als auch das immunhistochemische Expressionsmuster (TdT-, PAX-5-und CD56-Expression) können da-zu führen, dass v. a. der intermediäre Typ der MZK mit kutanen Manifestationen lymphoproliferativer Neoplasien verwechselt wird [30,31]. Buresh et al [32] …”
unclassified